Examination of Care Milestones for Preventing Congenital Syphilis Transmission Among Syphilis-Infected Pregnant Women in Alberta, Canada: 2017–2019. Issue 7 (26th July 2022) - Round, Jessica M.; Plitt, Sabrina S.; Eisenbeis, Lisa; Smyczek, Petra; Gratrix, Jennifer; Charlton, Carmen; Fathima, Sumana; O'Brien, Allen
Abstract : Congenital syphilis outcomes occurred in one-third of syphilis infected pregnant women in Alberta, Canada. Late treatment initiation and older maternal age were independently associated with a congenital syphilis outcome. Abstract : Background: An infectious syphilis outbreak in Alberta has resulted in increased congenital syphilis (CS) cases. To shed light on potential risk factors, we used administrative data sets to examine care milestones for the prevention of CS among pregnant women diagnosed with syphilis, as well as correlates of women giving birth to infants with CS. Methods: Provincial administrative databases were used to identify and describe pregnant women diagnosed with any stage of infectious or noninfectious syphilis who gave birth in Alberta between January 1, 2017, and December 31, 2019. Data on prenatal care, syphilis screening, and syphilis medication dispensation were used to evaluate the care milestones. Clinical care and maternal demographics were assessed using logistic and linear regression analyses to determine correlates for missed care milestones or a newborn outcome of CS. Results: Of 182 syphilis-infected pregnant women, 63 (34.6%) delivered a newborn with CS. Overall, in the first trimester, 136 (75.1%) women had a health care visit, 72 (39.6%) had a prenatal care visit, 71 (39.0%) were screened for syphilis, and 44 (24.2%) were treated. Gestational time to treatment initiation (adjusted odds ratio, 1.04; 95% confidence interval, 1.02–1.06) and older maternal age at diagnosis (adjusted odds ratio: 1.28, 95% confidence interval, 1.08–1.50) were independently associated with CS outcomes. No variables were found to be independently associated with a health care visit, prenatal screening, or initiation of treatment. Conclusions: Although nearly two-thirds of CS cases were prevented, there remained missed opportunities in the prevention of CS. Early treatment, which relies on timely access to prenatal care and screening, was the most important for the prevention of CS.